The Relationship Between Effective Communication Between Nurses and the Implementation of Patient Discharge Planning in the ASOKA Ward of Prof. Dr. Margono Soekarjo Purwokerto Regional General Hospital - Dhian Dwi Jayanti; Etlidawati (UM Purwokerto Press, 2026)
Background: Communication is a key effort to alter patient behavior, closely tied to health and care. Data from Asoka Ward at RSUD (Regional Public Hospital) Prof. DR. Margono Soekarjo in 2023 shows a total of 1,128 patients admitted. Observations in Asoka Ward indicate that nurse communication is still lacking in the implementation of discharge planning. This is evidenced by the incomplete conveyance of the discharge planning process to patients. Interviews with 20 patients in Asoka Ward revealed that only 4 (four) patients were aware of the discharge planning procedures at the hospital. Objective: To investigate the correlation between effective nurse communication and the implementation of discharge planning in Asoka Ward at RSUD Prof. DR. Margono Soekarjo, Purwokerto. Method: This study employed a correlational quantitative method with a cross-sectional approach. The population consisted of inpatients in Asoka Ward from January to December 2023. Using the Lemeshow formula, a sample of 97 respondents was determined. Results: The variables of communication and discharge planning in the